2005
DOI: 10.1097/01.cad.0000171769.43940.58
|View full text |Cite
|
Sign up to set email alerts
|

Somatic mutations in epidermal growth factor receptor underlying complete responsiveness to gefitinib in a Taiwanese female patient with metastatic adenocarcinoma of lung

Abstract: A 61-year-old never-smoker female suffered from adenocarcinoma of the lung with chest wall invasion and peri-adrenal lymph node metastases. After palliative resection of all clinically detectable primary and metastatic adenocarcinoma, she received cisplatin and gemcitabine combination chemotherapy for a total of 3 cycles. New metastatic lesions were found in spleen and para-aortic lymph nodes. Her tumor tissue was subjected to mutation analysis for epidermal growth factor receptor (EGFR) and had been shown to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…5 During the last few years, new molecularly targeted agents aimed to inhibit specific pathways and key molecules in tumor growth and progression have been developed. 18 Acquired mutations of EGFR gene in exons 18 to 21 and EGFR gene copy number, which is assessed by fluorescence in situ hybridization (FISH), could be used to predict a patient's responsiveness. 8 Ligand binding to EGFR leads to receptor TK activation and to a series of downstream signaling activation that mediate proliferation, migration, invasion, and suppression of apoptosis.…”
mentioning
confidence: 99%
“…5 During the last few years, new molecularly targeted agents aimed to inhibit specific pathways and key molecules in tumor growth and progression have been developed. 18 Acquired mutations of EGFR gene in exons 18 to 21 and EGFR gene copy number, which is assessed by fluorescence in situ hybridization (FISH), could be used to predict a patient's responsiveness. 8 Ligand binding to EGFR leads to receptor TK activation and to a series of downstream signaling activation that mediate proliferation, migration, invasion, and suppression of apoptosis.…”
mentioning
confidence: 99%
“…In non-small cell lung cancer (NSCLC), several reports have also shown that EGFR-specific tyrosine kinase inhibitors, such as gefitinib and erlotinib, are capable of reducing brain and adrenal metastases [ 22 , 23 ]. EGFR mutations, amplifications or gene gains have been associated with clinical responses to those inhibitors [ 18 , 24 ]. A previous study demonstrated that EGFR FISH analysis may be used as an alternative to gene mutation analysis as the primary laboratory test [ 25 ].…”
Section: Discussionmentioning
confidence: 99%